Radical Warfare’s First “Superweapon”: The Fears, Perceptions and Realities of the Orsini Bomb, 1858-1896 - Crossland, James (Terrorism and political violence, 2023)
This article retraces the forgotten legacy of a percussion triggered shrapnel scattering improvised explosive device (IED), known as the Orsini Bomb. Initially used in an attempt to assassinate Emperor Napoleon III in 1858, in the decades after, the Orsini Bomb was replicated, modified and deployed by regicides, insurgents and terrorists, and mythologised by the press as an omnipresent aspect of such forms of radical warfare. This article presents a “biography” of this unique IED, concluding, firstly, that Orsini’s design was an important point of reference in weapons manufacture for violent radicals even after the advent of dynamite in the 1860s and, secondly, that its reputation as a semiotic reference point for terrorist activity was enhanced by press reportage of its proliferation and use throughout the fin de siècle. In the final analysis, the Orsini Bomb became a transnationally recognised “brand” of weapon, synonymous with both assassination and insurgency. As such, the bomb’s reputation—often dwarfed in the historiography of political violence by dynamite—needs to be reconsidered.